2021
DOI: 10.18632/aging.203620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on primary liver cancer: epidemiology, pathogenesis and therapeutics

Abstract: Aging involves progressive physiological and metabolic reprogramming to adapt to gradual deterioration of organs and functions. This includes mechanisms of defense against pre-malignant transformations. Thus, certain tumors are more prone to appear in elderly patients. This is the case of the two most frequent types of primary liver cancer, i.e., hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA). Accordingly, aging hallmarks, such as genomic instability, telomere attrition, epigenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 136 publications
(139 reference statements)
0
25
0
Order By: Relevance
“…The pain in liver cancer patients is mostly severe and persistent, so analgesic measures are necessary. Many liver cancer patients have pain as a result of their treatment methods and drugs, and patients experience evident pain symptoms following surgical resection of their liver cancer, which has a significant impact on their daily lives [ 23 ]. The main method for relieving the pain of patients is drug analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The pain in liver cancer patients is mostly severe and persistent, so analgesic measures are necessary. Many liver cancer patients have pain as a result of their treatment methods and drugs, and patients experience evident pain symptoms following surgical resection of their liver cancer, which has a significant impact on their daily lives [ 23 ]. The main method for relieving the pain of patients is drug analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, though great heterogeneity was found in YPs and OPs, following the traditional cutoff age at 65 years old, no differences were found in efficacy endpoints between the two groups ( Table 2 and Figure 1 ), which is consistent with most previous studies. 23 , 24 , 37 , 39 , 40 Application of ICIs in other solid tumors suggested similar long-term outcomes in aged patients, following cut-off age at 70, 75, or 80 years, 41–44 which suggested promising prospect of application of ICIs in aging patients. However, age-related decreased performance status, complicated comorbidities, decreased function of solid organs (especially for aging liver with decreased ability of metabolism), immunosenescence, etc.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, participants from clinical trials might not accurately represent realworld situation of elderly patients, especially for whose age is ≥75 years. [22][23][24] Although previous studies have already investigated the application of sorafenib, lenvatinib monotherapy, or A+T in elderly patients with uHCC, [25][26][27][28] whether this group of patients would benefit from sorafenib or lenvatinib plus PD-1 inhibitors, needs to be clarified. In order to explore the efficacy and safety of sorafenib-or lenvatinib-based combination therapy with PD-1 inhibitors in elderly patients with uHCC, we conducted this study.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is a prognostic factor following liver resection and ablation therapy in patients with HCC [19,20]. Elderly patients who receive treatment for HCC are increasing [21] and also suffer complications of primary (age-related) sarcopenia and/or secondary (cancer-related or cirrhosis) sarcopenia.…”
Section: Introductionmentioning
confidence: 99%